Application of ascorbic acid in maintenance of minimally processed product quality of jackfruit (Artocarpus heterophyllus) - Md. Amirul Alam; Farzad Aslani; Siti Zaharah Sakimin; Siti Suhana Patrie; Abdul Shukor Juraimi (Bangladesh Botanical Society, 2017)
Physiochemical changes of minimal processing of jackfruit (Artocarpus heterophyllus Lam.) were studied by treating with different concentration of ascorbic acid (AA) and stored at different storage temperatures. Result showed that there were significant differences in fresh weight, firmness, ascorbic acid content, titratable acidity (TA), and soluble solid content (SSC), during increasing period of storage in both ambient and cold storage of minimal processed jackfruit. Treatment of different concentration of AA showed significant in fruit firmness, pulp fresh weight and AA content of minimal processed jackfruit kept under ambient temperature. Minimal processed jackfruit keeps under ambient storage exhibit greater fruit weight loss and softening as compared with cold storage. However, the AA content of minimal processed jackfruit increased in ambient storage and it was greater after one day treatment than cold storage fruit.